On the welfare effects of credit arrangements - Jonathan Chiu; Mei Dong; Enchuan Shao (Bank of Canada, 2012)
This paper studies the welfare effects of different credit arrangements and how these effects depend on the trading mechanism and inflation. In a competitive market, a deviation from the Friedman rule is always sub-optimal. Moreover, credit arrangements can be welfare-reducing, because increased consumption by credit users will drive up the price level so that money users have to reduce consumption when facing a binding liquidity restraint. By adopting an optimal trading mechanism, however, these welfare implications can be overturned. Price discrimination under the optimal mechanism helps internalize the price effects. First, small deviations from the Friedman rule are no longer welfare-reducing. Second, increasing the access to credit becomes welfare-improving. Finally, the model is extended to study the welfare effects of credit systems when credit serves as means of payment, and endogenous credit constraint.
Keywords: E40; E50; 330; Credit and credit aggregates; Payment; clearing; and settlement systems